Effect of Islamic ontology in life satisfaction among infertile women - Somaye Kazemian (Gonabad University of Medical Sciences, 2017)
Life satisfaction is an important and pervasive issue for all community members, including infertile women. Infertility brings about a mentally stressful situation. In this respect, life review therapy with emphasis on Islamic ontology may be an important factor in the promotion of life satisfaction and improvement of mental health. The study population included infertile women referred to the Mashhad Infertility Center. After completion of diagnosis process and conducting the pretest, 40 infertile women were randomly assigned to the groups of intervention and control. The participants completed the questionnaire of Miller life satisfaction of before and after the intervention. The intervention group received ten sessions of life review therapy while the control group was invited to attend the treatment sessions after the posttest. None of the members of two groups took any medication during the study period and they were followed up for three months to check the long-term effects. The results showed that life review therapy with emphasis on Islamic ontology can significantly increase life satisfaction in infertile women and potentially could be of clinical use. Considering the positive effect of life review therapy with emphasis on Islamic ontology in life satisfaction among infertile women, special trainings for these women and the preventive measures should be taken.